Gestational Weight Gain in Diabetic Women: Do Supportive Text Messages Make a Difference? [7E]. (May 2017) - Gupta, Angela; Buchanan, Christopher; Gavard, Jeffrey; Hostetter, Sarah; Miller, Collin; Mostello, Dorothea
Abstract : INTRODUCTION: Weight gain during pregnancy can lead to adverse health outcomes. The purpose of this study was to examine the effect of different text message regimens on gestational weight gain in women with diabetes. METHODS: Data from a prospective, controlled trial of women with gestational or Type 2 diabetes mellitus were analyzed. Women were randomized to receive either general pregnancy supportive text messages (Text4Baby) or diabetes-specific text messages (Text4Diabetes). Women also received nutrition education to limit their weight gain to the Institute of Medicine (IOM) gestational weight gain guidelines based on pre-pregnancy BMI. Groups were compared on gestational weight gain from study entry to delivery using independent students t-test, Kolmogorov-Smirnov, chi-square, and Fisher Exact tests. RESULTS: The final analysis had 71 patients: Text4Baby (n=35) and Text4Diabetes (n=36). Most women were obese at study entry (87.5%). Demographics did not differ between groups. There was no difference in maternal weight at entry, duration of participation, or total maternal weight gain. More women receiving Text4Baby text messages exceeded IOM guidelines for weekly weight gain compared to women receiving Text4Diabetes text messages (57.7% vs. 48.1%). Of all overweight and obese women, 52.8% gained more weight than IOM guidelines, while only 32.1% gained less and 15.1% gained within IOM guidelines. CONCLUSION: While general pregnancy and diabetes-specific text message groups did not differ in weight gain during pregnancy, most women in both groups gained more than IOM guidelines recommend. Text message interventions for women with diabetes in pregnancy should address the importance of avoiding excessive weight gain during pregnancy.